DEVELOPMENT OF AN ANDROID-BASED LAUNDRY APPLICATION SYSTEM WITH SELF-SERVICE FEATURES - Anis Lelitasari; Reza Ilyasa; Rifky Akbar Vetian; Rangga Gading Satria; Eko Kurniawan; Yudha Wibowo; Muhammad Roffi Suhendry; Wayan , Deva Adhisthanaya (JUTIM (Jurnal Teknik Informatika Musirawas), 2025)
The increasing societal mobility and consumer demand for independent solutions have amplified the need for efficient and convenient laundry services. Traditional laundry operations often struggle with common issues such as long waiting times, potential order inaccuracies, and limited transparency. The primary objective of this research was to develop an Android-based laundry application system featuring robust self-service capabilities. This application empowers customers to seamlessly perform online ordering, secure digital payments, and real-time laundry status tracking, effectively minimizing the need for direct staff intervention. This innovative approach is designed to significantly reduce customer wait periods and enhance the precision of order data. The system was developed using the systematic Waterfall Model. The process involved in-depth requirements analysis, detailed system design, program code implementation, and thorough testing to ensure optimal and bug-free operation. The culmination of this research is a functional prototype of the Android-based application, featuring an intuitive interface and comprehensive self-service functions. This application is expected to both enhance the operational efficiency for laundry providers and deliver a more practical, modern, and independent experience for users managing their laundry needs.